STAM Prolongs Clear Cell Renal Cell Carcinoma Patients' Survival via Inhibiting Cell Growth and Invasion - Deng, Tuo; He, Zihao; Duan, Xiaolu; Gu, Di; Cai, Chao; Wu, Wenqi; Liu, Yongda; Zeng, Guohua (Frontiers in Oncology, 2021)
Background: Signal transducing adaptor molecule 1 (STAM1) was considered to mediate cell growth and be involved in multiple signaling pathways; however, no researches on the role of STAM1 in any tumors have been published yet. Our study aimed to investigate the prognostic value of STAM1 for clear cell renal cell carcinoma (ccRCC), and its role in modulating cancer cell function. Methods: Data from The Cancer Genome Atlas (TCGA) in December 2019 were used to examine the role of STAM1 in indicating ccRCC patients’ survival. A purchased tissue microarray (TM) and fresh ccRCC renal tissues were used for further validation. Then STAM1 was overexpressed in human ccRCC cell lines for in vitro-assays. Finally, bioinformatics was performed for STAM1 protein-protein interaction (PPI) network construction and functional analyses. Results: A total of 539 ccRCC and 72 control samples were included for TCGA cohort, and 149 ccRCC and 29 control slices were included for TM cohort. In TCGA and TM cohorts, we found STAM1 expression was lower in ccRCC compared with normal adjacent non-cancerous renal tissues (P < 0.0001 for both two cohorts). STAM1 downregulation was also related to significantly shorter overall survival (OS) (P < 0.0001 for both two cohorts) and more aggressive tumors. In TCGA cohort, reduced STAM1 expression was also associated with aggressive features of the tumor. Under multivariate analyses, STAM1 was demonstrated to be an independent prognostic factor for ccRCC survival in both TCGA (HR = 0.52, 95%CI:0.33-0.84, P = 0.007) and TM cohorts (HR = 0.12, 95%CI:0.04-0.32, P < 0.001). Our in vitro-experiments showed that STAM1 inhibited cell viability, invasion and migration in ccRCC cell lines. In PPI network, 10 candidate genes categorized into 5 biological processes were found to be closely related to STAM1. Conclusion: STAM1 is a promising prognostic biomarker for predicting ccRCC survival outcomes. Preliminary pathogenesis is demonstrated by our in vitro-experiments. Further pathological mechanisms of STAM1 in modulating ccRCC require comprehensive laboratory and clinical studies.